Models of Social Exploitation with Special Emphasis on Slovenc Traffic Economics - Iztok Ostan (Promet (Zagreb), 2005)
In order to decipher the organisational behaviour operatingin the transport sector of the economy it is necessary to discoverthe prevalent patterns of social exploitation at work. PreliminaJyresults of a study of experienced irregular traffic studentsshow that, according to them there is no significant differencein Slovenia between exploitation in traffic and other sectors.Thus, general models of exploitation could be used to explainthe behaviour in the traffic sector. Empirical research amongSlovene students showed that according to their statements inthe 90s the managerial and capitalistic types of exploitation prevailedin Slovenia over non-exploitative types of economic behaviour.It also showed that statements of students do not differmuch from those of the general public regarding this question,nor from the statements of irregular students with extensivework experience. It was also found that there were no substantialdifferences between the statements of Italian and Slovenestudents regarding the type of exploitation operative in theircountries. Students of traffic are basically of the same opinionregarding this topic as students in general, though slightly morecritical, especially towards business managers and politicians.